1996
DOI: 10.1620/tjem.180.233
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Amino Acid Sequences of Hepatitis B Virus S Gene in 46 Children Presenting Various Clinical Features for Immunoprophylaxis.

Abstract: We compared amino acid sequences of hepatitis B virus (HBV) S protein deduced from analyzed DNA sequence in 46 children who received immunoprophylaxis to prevent mother-to-child transmission of HBV. They were classified into 6 groups by their clinical features. The antibody escape mutants were found in 8 cases among 46 cases. We studied the difference in clinical features in these cases and speculated that 126 Ser or 140 Ser-strain may have a different behavior in relation to antibody to hepatitis B surface an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Each serum sample (100 l) was incubated at 65°C for 2 hr in the presence of proteinase K (150 g/ ml), 0.5% sodium dodecyl sulfate, 5 mM ethylene diamine tetra-acetic acid, and 10 mM Tris-HCl (pH 8.0). TTV DNA was extracted from the serum using the phenol-chloroform-isoamyl alcohol procedure described previously [Miyake et al, 1996]. Extracted DNA was precipitated with cold ethanol in the presence of carrier transfer RNA (5 g) and was dissolved in 50 l of 10 mM Tris-HCl (pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…Each serum sample (100 l) was incubated at 65°C for 2 hr in the presence of proteinase K (150 g/ ml), 0.5% sodium dodecyl sulfate, 5 mM ethylene diamine tetra-acetic acid, and 10 mM Tris-HCl (pH 8.0). TTV DNA was extracted from the serum using the phenol-chloroform-isoamyl alcohol procedure described previously [Miyake et al, 1996]. Extracted DNA was precipitated with cold ethanol in the presence of carrier transfer RNA (5 g) and was dissolved in 50 l of 10 mM Tris-HCl (pH 8.0).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was extracted from 100 l of the serum obtained from each patient using the phenol-chroloformiosamyl alcohol procedure described previously [Miyake et al, 1996]. Seminested PCR was performed using a set of primers synthesized according to the published TTV sequence [Okamoto et al, 1998].…”
Section: Methodsmentioning
confidence: 99%
“…Mutations near the MHR can alter group-specific antigenicity even though the mutations are not within the MHR. [899495] Monoclonal antibody binding assays have also shown that residues 178-186 are exposed on the surface of the 20 nm particle. [96] This is the region which specifies the q sub-determinant.…”
Section: Escape Mutantsmentioning
confidence: 99%